2012
DOI: 10.1503/cjs.036010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatic hydatid disease complications using endoscopic retrograde cholangiopancreatography procedures

Abstract: Background: Liver hydatidosis may lead to serious morbidity due to biliary complications, the management for which endoscopic sphincterotomy (ES) and biliary drainage are very efficient. We evaluated the effectiveness of endoscopic treatment for complications of hepatic hydatid disease. Methods:We retrospectively reviewed endoscopic retrograde cholangiopancreatography (ERCP) procedures performed between January 2000 and December 2009 and compared laboratory findings, localization of the lesions and ERCP proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
2
10
0
3
Order By: Relevance
“…All cases of biliary leakage ceased in 2-21 days. The most commonly performed procedure in that study was ES (23). In our study, bile leaks were closed in an average of 19 days after ERCP, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All cases of biliary leakage ceased in 2-21 days. The most commonly performed procedure in that study was ES (23). In our study, bile leaks were closed in an average of 19 days after ERCP, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…One study reported the management of seven patients with CE developing obstructive jaundice and cholangitis after surgery, who were treated by ERCP. Within 36 hours of ES and clearing of the biliary tract of debris, normal bile flow was achieved and symptoms related to biliary obstruction were resolved (23). In our series, ERCP was performed in three patients in the postoperative period for biliary obstruction.…”
Section: Discussionmentioning
confidence: 79%
“…Today, endoscopic interventions are the mainstay of treatment in patients with unclosed or high-flow fistulas. It is believed that endoscopic sphincterotomy causes the early closing of the fistula by lowering intrabiliary pressure [13]. There is no definite conclusion about the timing of the endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Although many new treatment procedures are now in use, the postoperative complication rate still remains very high [19, 23, 30, 31]. The most frequent serious postoperative complications are prolonged persistence of a residual cystic cavity, cystic cavity infections, biliary peritonitis, and biliary fistulas.…”
Section: Discussionmentioning
confidence: 99%